Sustainable STEM Education for Disadvantaged Communities. - Liew, Chin Ying; Ling, Siew Eng; Tang, Howe Eng; Gail Leask, Marilyn (Pertanika Journal of Social Sciences & Humanities, 2026)
Disadvantaged local communities frequently face significant barriers to recognising the value of STEM education and are hesitant to engage in partnerships with external organisations due to mistrust or unfamiliarity. As a result, students from these communities miss opportunities to enhance their learning and career prospects, thereby creating a gap compared to urban students who have better access to innovative programmes, mentorships, and STEM career pathways. This study aims to bridge the gap by exploring the perceptions of disadvantaged communities regarding factors influencing students' performance in STEM education. It also examines their level of involvement in STEM programmes and explores the issues they faced in accessing and engaging with such education. The study involved 11,827 respondents, who were the local communities of 1,224 primary and secondary schools. Using a mixed-methods approach, quantitative data were collected through surveys, and qualitative data were gathered through in-depth interviews. The findings indicate that these communities tend to leave the responsibility for STEM education to teachers, schools, and students. Key obstacles to their partnership include gaps in STEM knowledge, a mindset toward STEM education, and cultural factors that hinder progress in STEM education within disadvantaged communities. Consequently, a local community STEM education model is proposed as a holistic approach to sustaining STEM education by strengthening community support in these communities.